Being a therapist, becoming a researcher: A collaborative autoethnography on the experiences of novice researchers - Lorås, Lennart; Lindeman, Sari; Breden, Andreas; Almeland Hansen, Hege (European Journal for Qualitative Research in Psychotherapy, 2022)
The aim of this study was to explore how four professionals, both therapists and academics, experienced the transition to becoming a researcher. Collaborative autoethnography gave us the opportunity to gain a collective understanding of our shared experiences (Ngunjiri et al., 2010). The data were analysed using reflexive thematic analysis and resulted in four themes: (1) academia as a hierarchical system, (2) realizations about becoming a researcher, (3) a meaningful career choice, and (4) self-development. Research output turns out to be the most important criterion in academia. Employees in high-status positions like associate and full professor are therefore at the top of the hierarchy. At the same time a lot of teaching tasks need to be performed. Teaching is most often done by employees with less formal competence. This creates tensions. A tension that seems to be inevitable, as research is both a requirement and high in status, while teaching is one of the core tasks. Becoming a researcher is a demanding process on both a personal and relational level due to high expectations. All the same, research positions offer a relatively large degree of freedom and the possibility to organize the workday. The process of becoming a researcher was therefore described as meaningful, as it provided considerable opportunities for self-development.